Genetic engineering of Saccharomyces cerevisiae for polysaccharide degradation - Petersen, Shaunita Hellouise,1971- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1998.